Efficacy of Vitamin-D Supplement on Thyroid Profile in Children with Graves’ Disease - Pratita, Winra; Arto, Karina Sugih; Arto, Nindia Sugih (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Many studies have shown low Vitamin-D level as a risk factor for autoimmune diseases, especially multiple sclerosis and thyroid disease. Graves’ disease (GD) is an autoimmune disease caused by autoantibodies that stimulate thyroid-stimulating hormone (TSH) receptors by increasing thyroid hormone synthesis and secretion. Several studies report that many patients with autoimmune thyroid disease including GD have low Vitamin-D status. AIM: The objective of the study was to evaluate the effect of Vitamin-D supplement on GD patients on improvement in thyroid hormone levels. METHODS: Open random clinical trial was conducted in GD patients to determine changes in thyroid hormone to achieving normal levels between those receiving methimazole plus Vitamin-D supplementation compared with those who only received methimazole. Patients were checked for TSH receptor antibody, thyroid profile and Vitamin-D level before treatment and rechecked for thyroid profile and Vitamin-D level 3 months after treatment. t-test used to compare the drug efficacy (p < 0.05) in two groups. RESULTS: From 25 children with GD accompanied by Vitamin-D deficiency with an average value of Vitamin-D was 16 ng/mL. GD children who receive methimazole with Vitamin-D supplement had elevated TSH levels in the 3rd month of therapy that was significantly different compared to GD children who received methimazole only (p = 0.00), and the increase of TSH was also followed by an increase in Vitamin-D levels. CONCLUSION: All children with GD had Vitamin D deficiency, and the addition of Vitamin-D supplement to GD therapy would improve TSH faster than children who did not receive Vitamin-D supplement.